Fallicambarus (F.) wallsi (Decapoda: Cambaridae), a new burrowing crayfish from eastern Texas - Johnson, Daniel P. (Zootaxa, 2011)
Fallicambarus (F.) wallsi is described from San Augustine and Sabine counties, Texas. It may be distinguished from its nearest relative, F. (F.) kountzeae, by its distomesially oriented proximal margin of the cheliped’s palm mesial to the condyle; proportionately longer mesial margin of the palm; lack of a distinct excision on the dactyl’s opposable margin; more strongly tapering mesial process and absent or reduced cephalic process of the first pleopod of the first form male; and proportionately broader mesial ramus of the uropod, antennal scale and areola. An identification key is provided for the subgenus Fallicambarus.